The Anomaly OF Airline Passenger Behavioral Intention: A Comparison Between Low-Cost and Full-Service Airlines - Maulisa, Auryn Rachma; Hijrah Hati, Sri Rahayu (ASEAN Marketing Journal, 2021)
Manuscript type: Research paper Research Aims: This study investigates the effect of service quality, perceived value for money, and customer satisfaction based on behavioral intentions to re-use, be loyal, and to recommend the airlines to others, in low-cost and full-service airlines. Design/methodology/approach: The online survey was conducted to 161 low-cost and 156 full-service airline passengers Research Findings: The study indicates that the most robust variable that influences the airline passengers’ behavioral intention is customer satisfaction. The study also indicates that customer satisfaction has a positive impact on passengers’ behavior intention in both the low cost and full-service customer groups. The study shows an anomaly in regard to the effect of value for money and service quality on behavioral intention. Although it is expected that perceived value for money will positively and significantly influence behavioral intention of low-cost airline customers, the study found that the impact of the variable is not significant in this customer group. In contrast, it is predicted that service quality will have a more positive impact on full- service airline passenger, but the study found no direct effect of the variable on the customer behavioral intention. Theoretical Contribution/Originality: The study will shed light on the relative importance of value for monet and service quality in the market where the low-cost carrier become the key players. Practitioner/Policy Implication: The results indicate that the characteristics and the antecedents of the behavioral intention of the airline passenger might have changed. Therefore, the airline company should make some adaptation on their marketing strategy especially in regard to the pricing and service quality. Research limitation/Implications: This study only distinguishes between low-cost and full- service airlines in general, without really considering the brand specifics of each airline. Thus, an inaccurate picture of a specific brand may be presented, since the performance of each brand is so different. The future researcher can investigate the robustness of the model and relationships among variables among different airlines brand.